Additional pitfalls of using 1, 1‐ADEQUATE for structure elucidation. (10th July 2016) - Cohen, Ryan D.; Saurí, Josep; Huff, Chelsea A.; Krska, Shane W.; Martin, Gary E.
Abstract : 1, 1‐ADEQUATE is a powerful and robust NMR experiment to establish carbon–carbon connectivities using modest sample quantities when cryogenic probe technology is available. Yet potential pitfalls of applying this method are not widely appreciated, such as weak or missing 1 J CC correlations in strongly coupled 13 C‐ 13 C AB spin systems and unusually large multi‐bond ( n J CC ) correlations associated with particular functional groups. These large n J CC correlations observed in 1, 1‐ADEQUATE spectra could be mistaken for 1 J CC correlations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : For pyrazine ring containing systems, the 3 J CC coupling is unusually large and can lead to observable cross peaks in 1, 1‐ADEQUATE spectra. Further difficulties arise for 13 C‐ 13 C AB spin systems as the 1 J CC correlation may be missing or of similar magnitude as large n J CC couplings. Here, we present an unusual case study of methyl‐5‐(hydroxymethyl)‐6‐[(2, 2, 2‐trifluoroethyl)sulfanyl]pyrazine‐2‐carboxylate where the 1 J CC correlation was completely absent from the INADEQUATE spectrum yet measurable using the J‐modulated 1, 1‐ADEQUATE method.